ANALISIS HUKUM ISLAM TERHADAP PERTIMBANGAN HAKIM DALAM PUTUSAN CERAI GUGAT KARENA NAFKAH TIDAK LAYAK - Hardina; Darwis, Muhammad; Suhayib (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2025)
The concept of the Islamic family does not differentiate between the rights and obligations of husbands and wives. Both spouses possess reciprocal rights and responsibilities, and each is entitled to fair treatment from the other. Consequently, when one party perceives that their rights are not being fulfilled, it may lead to a breakdown of the marital relationship and result in divorce. This study is the library-based research employing a normative legal approach.